Partial substitution in the hidden curriculum of children’s media: a comparative corpus analysis of religion-oriented and general-educational Turkish public broadcasting - Ramazan Şimşek (Frontiers in Psychology, 2026)
Research on social–emotional learning (SEL) has accumulated extensive evidence on programmatic outcomes but devoted less attention to the lexical-semantic shape of the educational input that children actually encounter. This study asks how religion-oriented and general-educational children’s broadcasting operationalize SEL competencies at the level of vocabulary. Two Turkish public children’s broadcasters, TRT Çocuk and TRT Diyanet Çocuk, were compared. The two share institutional auspices, regulatory oversight, target age range and broadcast format, yet differ systematically in curricular orientation (general-educational vs. religion-oriented). A 225,451-token comparable corpus (112,983 + 112,468; 24 series, 284 episodes) was analyzed using standard corpus-linguistic measures over morphologically lemmatized Turkish text: Simple Maths keyness, Gries’s deviation of proportions for dispersion, and collocation within a ± 5 token window. Pre-registered Mann–Whitney U tests with Bonferroni-Holm correction served as convergence indicators. The five CASEL competencies appeared in both channels at comparable rates (all SM ≤ 1.31; all DP < 0.18). Schwartz value axes diverged: tradition (SM = 2.50) and benevolence indexed the religion-oriented profile, whereas achievement (SM = 1.37) marked the general-educational channel. The most pronounced pattern emerged in self-regulation. Religious self-regulation appeared at SM = 7.94 in TRT Diyanet Çocuk (G 2 = 656.2; Holm-corrected p < 0.001; rank-biserial |r| = 0.96). Secular self-regulation showed only a modest TRT Çocuk lead that did not reach inferential significance (SM = 1.56, p_adj = 0.423, null preserved). A theoretical concept of partial substitution is proposed to capture a pattern that neither a supplementation nor an outright displacement account describes: the religious repertoire gains dominance without fully crowding out secular techniques. Findings contribute to the input-characterization line in educational psychology with Turkish empirical material and offer implications for culturally responsive SEL curriculum design.